Trait Rumination Influences Neural Correlates of the Anticipation but Not the Consumption Phase of Reward Processing - Kocsel, Natália; Szabó, Edina; Galambos, Attila; Édes, Andrea; Pap, Dorottya; Elliott, Rebecca; Kozák, Lajos R.; Bagdy, György; Juhász, Gabriella; Kökönyei, Gyöngyi (Frontiers in Behavioral Neuroscience, 2017)
Cumulative evidence suggests that trait rumination can be defined as an abstract information processing mode, which leads people to constantly anticipate the likely impact of present events on future events and experiences. A previous study with remitted depressed patients suggested that enhanced rumination tendencies distort brain mechanisms of anticipatory processes associated with reward and loss cues. In the present study, we explored the impact of trait rumination on neural activity during reward and loss anticipation among never-depressed people. We analysed the data of 37 healthy controls, who performed the monetary incentive delay task which was designed for the simultaneous measurement of the anticipation (motivational) and consumption (hedonic) phase of reward processing, during functional magnetic resonance imaging (fMRI). Our results show that rumination - after controlling for age, gender, and current mood - significantly influenced neural responses to reward (win) cues compared to loss cues. Blood-oxygenation-level-dependent (BOLD) activity in the left inferior frontal gyrus triangularis, left anterior insula and left rolandic operculum was positively related to Ruminative Response Scale (RRS) scores. We did not detect any significant rumination-related activations associated with win-neutral or loss-neutral cues and with reward or loss consumption. Our results highlight the influence of trait rumination on reward anticipation in a non-depressed sample. They also suggest that for never-depressed ruminators rewarding cues are more salient than loss cues. BOLD response during reward consumption did not relate to rumination, suggesting that rumination mainly relates to processing of the motivational (wanting) aspect of reward rather than the hedonic (liking) aspect, at least in the absence of pathological mood.